The Impact of Employment Law on Human Resource Practices: A Global Perspective - Hasyim, Hasyim; Bakri, Muhammad (The Journal of Business and Management Research, 2023)
This study explores the significant impact of employment law on human resource (HR) practices, focusing on how legal frameworks shape HR management, organizational culture, and employee well-being. A qualitative research design was utilized, involving semi-structured interviews and focus groups with HR professionals, legal experts, and employees from multinational corporations. Thematic analysis was used to identify patterns and themes related to legal compliance and HR strategies. The findings reveal that legal frameworks mandate compliance and significantly shape HR practices, influencing safety, diversity, inclusion, and employee well-being. Stringent safety regulations improve workplace safety and foster trust and accountability. Robust family leave policies enhance employee loyalty and productivity, while anti-discrimination laws promote diverse and inclusive cultures. These findings support the hypothesis that legal compliance positively impacts HR practices and organizational outcomes and align with existing theoretical models emphasizing the multifaceted interactions between employment law and HR practices. The research contributes to both academic literature and practical HR management by highlighting the importance of integrating legal compliance into HR strategies to create resilient and adaptive practices in complex legal environments. Managers and policymakers can use these findings to develop effective HR policies that support employee well-being and organizational success. Future research should use quantitative methods to validate these findings and explore the long-term impacts of legal compliance on organizational performance.